KEKERASAN SIMBOLIK MEDIA TERHADAP ANAK - Munfarida, Elya (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2010)
Various social anomalies that occurred in this nation can represent the people (individuals) who are "sick". Thevalues of this nation in reality have not been able to effectively stem the rampant phenomenon of anomalies above. Variousfactors can cause the condition, such as ineffective value education in schools, families or communities; ungroundeddakwah; or media that is not impartial public interest. Media as one of information tools, considered to have significantinfluence to child's destructive and deviant behavior. Programs that aired in fact be counterproductive to the improvementof children's human qualities. This can be seen from several cases of child abuse and sexual harassment was motivated bythe impression of violence and pornography in the media. In this context, this paper tries to study the symbolic violence frommedia to the children (world) by presenting programs of violence and pornography in its various forms. Economic interests ofpolitical domination has made the media ignores the public interest, especially children by creating programs that do noteducate and inculcate the values of violence